2009
DOI: 10.1007/s00268-009-0253-6
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Outcomes Auditing Systems in Humanitarian Organizations

Abstract: The current outcomes evaluation system has proven beneficial in tracking patient outcomes, auditing surgical performance, and providing feedback to surgeons and other team members. Challenges are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 42 publications
3
36
1
Order By: Relevance
“…In part, this is due to a difficulty with follow-up. Of 4,100 operations for cleft lip and palate by 1 organization in 40 simultaneous sites, for example, only 703 patients (17 %) returned for a 6- to 9-month postoperative visit [19]. Similarly, in a Spanish-African cooperation program for the repair of hernias, follow-up was 21 % [16].…”
Section: Resultsmentioning
confidence: 99%
“…In part, this is due to a difficulty with follow-up. Of 4,100 operations for cleft lip and palate by 1 organization in 40 simultaneous sites, for example, only 703 patients (17 %) returned for a 6- to 9-month postoperative visit [19]. Similarly, in a Spanish-African cooperation program for the repair of hernias, follow-up was 21 % [16].…”
Section: Resultsmentioning
confidence: 99%
“…Follow-up rates have been correspondingly low: among medical mission groups that do provide postoperative care, rates range from 5% to 35% of patients [58]. Cleft missions groups have made progress in monitoring surgical outcomes, for instance through the development of outcomes databases [18, 43, 49, 62]. However, an increased focus on outcomes is needed.…”
Section: Building Capacity While Addressing Specific Needs: a Diagmentioning
confidence: 99%
“…7,13,14 Can such a methodology be employed in a charitable mission setting? While the feasibility of studies involving medical mission patients with interviews and follow-up has been demonstrated, 5 no prospective satisfaction study has yet been conducted with medical mission patients. We therefore conducted a small prospective cohort study containing both these elements, assessing the relationship between pre-operative expectations and post-operative outcomes and level of satisfaction in parents of children receiving cleft lip or cleft palate (CL/CP) repair from surgeons of the Operation Smile team in Tegucigalpa, Honduras.…”
Section: Introductionmentioning
confidence: 98%
“…One large and well known agency, Operation Smile, has provided CL/CP repairs in developing countries since 1982. 4,5 With CL/CP repair teams consisting of plastic surgeons, anaesthetists and other health-care professionals, and the co-operation of local surgeons and volunteers, Operation Smile may perform 200 operations during a 1-week trip. Families travel many miles to reach the surgical facility so that their children can receive medical care they could not otherwise afford.…”
Section: Introductionmentioning
confidence: 99%